1994
DOI: 10.1007/bf02001917
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan loss and subsequent replenishment in articular cartilage after a mild arthritic insult by IL-1 in mice: Impaired proteoglycan turnover in the recovery phase

Abstract: The reparative responses of articular cartilage after an arthritic insult have not been studied extensively to this day. In the present study, we injected interleukin-1 (IL-1) into knee joints of mice to provoke a mild and transient arthritic insult, and characterized both the catabolic and the subsequent recovery phase. In the catabolic phase, which lasted 2 days after IL-1 injection, proteoglycan (PG) breakdown was profoundly accelerated and PG synthesis was markedly inhibited. Sulfation and polysaccharide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The reduced proteoglycan production may significantly contribute to osteoarthritis since it may lead to further changes in the components of cartilage matrix and the rate of matrix turnover in Smad3 ex8/ex8 mice. Interestingly, the decreased levels of proteoglycans associated with Smad3 deficiency is similar to that caused by the IL-1 overexpression (van de Loo et al 1994, van de Loo et al 1998). This suggests partial overlapping roles between IL-1 and TGF-β/Smad3 in osteoarthritis initiation and progression.…”
Section: Discussionmentioning
confidence: 66%
“…The reduced proteoglycan production may significantly contribute to osteoarthritis since it may lead to further changes in the components of cartilage matrix and the rate of matrix turnover in Smad3 ex8/ex8 mice. Interestingly, the decreased levels of proteoglycans associated with Smad3 deficiency is similar to that caused by the IL-1 overexpression (van de Loo et al 1994, van de Loo et al 1998). This suggests partial overlapping roles between IL-1 and TGF-β/Smad3 in osteoarthritis initiation and progression.…”
Section: Discussionmentioning
confidence: 66%
“…Early stages of cartilage degeneration are associated with a loss of proteoglycans [ 41 ], collagen network integrity [ 42 ], and cartilage surface integrity [ 43 ]. In both primary and secondary cartilage degeneration the earliest alterations include surface irregularity formation, erosion, and fissuring and may be consistently detected by OCT. OII as a measure surface irregularity was the only OCT parameter to be significantly affected by impaction, that is, high-energy impact, whereas OHI and OAI were not.…”
Section: Discussionmentioning
confidence: 99%
“…13 It has been shown that PG, which provides the compressive stiffness of articular cartilage, is a marker of cartilage health. Because its depletion has been associated with early pathologic changes in articular cartilage and osteoarthritis, 2325 the ability to measure PG content could permit detection of poor cartilage health, early cartilage damage, or early degenerative changes before these changes were allowed to progress to more advanced joint degeneration.…”
Section: Introductionmentioning
confidence: 99%